2018
DOI: 10.3390/ijerph15112552
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depressive Mood During Acute Chikungunya Infection in Primary Healthcare Settings

Abstract: Background: We aimed to screen for depressive mood experienced during acute chikungunya (CHIKV) infection, and to evaluate the association of several exposures with the risk of depressive symptoms. Methods: A cross-sectional analysis of a multicenter cohort study took place and data from 354 adult individuals with confirmed CHIKV infection were analyzed. Participants were recruited in primary health care settings and the Patient Health Questionnaire-2 (PHQ-2) was used. Prevalence odds ratios (OR) and 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(30 reference statements)
0
6
0
2
Order By: Relevance
“…Although the psychic complaints brought by this study have multifactorial characteristics, research increases their association with the chronicity of CHIK. According to the authors, persistent pain in these cases is one of the most important risk factors for depression, and mood disorders, in addition to gastrointestinal manifestations 31 . Thus, this study draws the attention of health professionals to the need to consider the elements of physical and psychic nature when preparing their therapeutic plans.…”
Section: Resultsmentioning
confidence: 99%
“…Although the psychic complaints brought by this study have multifactorial characteristics, research increases their association with the chronicity of CHIK. According to the authors, persistent pain in these cases is one of the most important risk factors for depression, and mood disorders, in addition to gastrointestinal manifestations 31 . Thus, this study draws the attention of health professionals to the need to consider the elements of physical and psychic nature when preparing their therapeutic plans.…”
Section: Resultsmentioning
confidence: 99%
“…In some patients with neurological involvement, there may be psychiatric symptoms such as confusion, delirium, disorientation, and even psychosis 57 . However, few studies have reported specific psychiatric manifestations of acute CHIK, including mania and depression [58][59][60] . Mania has been reported in a patient with acute CHIK who was previously diagnosed with bipolar disorder, although the patient was stabilized with valproic acid 58 .…”
Section: Psychiatric Manifestationsmentioning
confidence: 99%
“…Depression in acute CHIK affects up to half of the patients. Younger patients and those with severe arthritis and gastrointestinal symptoms are more likely to self-report depression 60,61 .…”
Section: Psychiatric Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sendo assim, a ausência ou mesmo a inadequação do tratamento, em alguns casos, podem causar disfunção de sistemas orgânicos, em particular o osteoarticular, dificultando desde o caminhar até cuidados pessoais como vestir roupas, pentear os cabelos, tomar banho, entre outros, gerando uma piora da qualidade de vida, principalmente em pacientes idosos e portadores de doenças osteodegenerativas (COUTURIER et al, 2012;HUA;COMBE, 2017). Além do comprometimento orgânico, a saúde mental mostra-se abalada nesse grupo de usuários, em especial com o desencadeamento de insônia, depressão e ansiedade (MURILLO-ZAMORA et al, 2018).…”
Section: Introductionunclassified